Changing Footings on 'Jacob's ladder': dealing with sensitive issues in dual-role mediation on a Swedish TV show. - Englund Dimitrova, Birgitta (Perspectives: Studies in Translatology, 2019)
This case study examines a Swedish TV interview with a Soviet pop singer in 1985 where the talk show host, who is both a trained interpreter and an experienced media journalist, acts as a dual-role mediator, interviewing and interpreting at the same time. The analysis is contextualized within the political and military relations between Sweden and the USSR in the 1980s. Theoretically, the study draws on ethics of interpreting, ethics of entertainment and the notions participation status or footing. A potential challenge for a dual-role mediator is that two different ethical stances are involved; here, ethics of entertainment (entertainment, comfort, culture value orientation) and ethics of interpreting (impartiality, neutrality, accuracy). These may clash, but the study claims that the different stances can also be used to the participants' advantage. Here, the role of talk show host dominates over the role of interpreter, and interpreting ethics can be flouted and played with if it suits the purposes of the former. The study shows the complexity of dual-role mediation and emphasizes the need to take into account the perspectives of both of the involved roles in research on participants' interaction and changes of footing.